In-vitro study of hybrid silver nanoparticles with humic acid extracted from cow dung against pathogens - Shabir Ahmed Dharejo; Tajnees Pirzada; Muhammad Raza Shah; Ahmed Nadeem; Khalid Hussain Thebo (Heliyon)
Recently, researchers have used silver nanoparticles (AgNPs) coupled with humic acid (HA) as antimicrobial agents. Herein, AgNPs were prepared and coupled with humic acid for their antimicrobial activities. The as-prepared AgNPs coupled with humic acid (HA) were characterized by an atomic force microscope (AFM), X-ray powder diffraction (XRD), zeta potential, zeta sizer, Fourier-transform infrared (FT-IR) spectroscopy, and UV–VIS spectrophotometer. Moreover, human plasma, varied salt concentrations, and pH levels were used for stability confirmation using a UV–VIS spectrophotometer. The antibacterial activities and minimal bactericidal concentration (MBC) of coupled AgNPs were determined by disk diffusion and broth dilution methods, respectively, against identified Staphylococcus aureus, Streptococcus pyogene, Pseudomonas aeruginosa, and Escherichia coli, which are extracted from cow dung. AgNPs' peak in the UV–Vis spectral range showed maximal absorption at 415 nm. The coupled AgNPs displayed their distinctive peak under all circumstances, demonstrating their stability. The FT-IR displayed functional groups such as hydroxyl, carboxylic acids, carbonyl, ester, and ether groups. The particles were face-centered cubic (FCC) in structure, according to the XRD. Moreover, particles had a spherical shape, high negative zeta potential, and were polydisperse in nature, with an average size of 25.43 nm. The minimal bactericidal concentration (MBC) of AgNPs was found to be 2.5 mg/mL, and the MBC of AgNPs/HA was found to be 5 mg/mL. The result indicated that the as-synthesizedAgNPs/HA are more effective in inhibiting all the studied microorganisms, which can be attributed to the therapeutic use of nanoparticles coated with humic acids.